(untitled) (Quinto Sol, 2025)
This article analyzes aspects of the prolific intellectual career of Alexis Peyret, a French revolutionary based in the Río de la Plata region who held various institutional positions during the third quarter of the 19th century. We examine his participation in the political debate of the 1860s and 1870s and his appreciation of historical narratives, in order to demonstrate how his conceptions of "federalism" and the recent past allow us to consider the originality of his discourse. We approach this work in three sections: first, we generally describe Peyret’s itinerary and his insertion into the political landscape of the time; then, we highlight his central role in the translation and dissemination of Pierre-Joseph Proudhon’s concepts and how he projected them with his own particularities; finally, we reconstruct the uses of the past that Peyret promoted, producing alternative perspectives to those of his contemporaries. All of this will allow us to appreciate the unique place the intellectual occupied in the concert of emerging liberal ideas that radiated throughout the region, and how, from that perspective, the events that occurred in Entre Ríos following the assassination of Justo José de Urquiza and the latest federal rebellions were interpreted.